Sanctioning an unruly ally: Understanding Sino-North Korean trade through the People's Daily - Weifeng Zhong (American Enterprise Institute (AEI), 2018)
Using the texts of the People's Daily, an official publication of the Communist Party of China, the author shows that the socialist alliance between China and North Korea has significantly weakened since the Korean War.
Keywords: A; 330; International trade; China; North Korea